Implementing Internal Public Service through a Risk-Based Employee Medical Check-Up (MCU) Program - Fikri, Ady; Fitriah, Nurul; Alfitri, Alfitri; Putra, Raniasa; Lionardo, Andries (UIN Sunan Gunung Djati, 2026)
This study analyzes the implementation of an employee Medical Check-Up (MCU) program as an internal public service in a regional public hospital in South Sumatra, given the rising risk of non-communicable diseases among the working-age population and the limited use of MCU outputs for evidence-based occupational health policy. The study applies a qualitative document analysis approach using official MCU implementation records for the 2025 cycle, including the service flow, the schedule of 664 participants across more than 130 work units, a risk-based examination matrix, an aggregation of 124 health findings, and employee attendance records. Data were analyzed through thematic content analysis based on a policy implementation lens.. The MCU is implemented through standardized procedures, a rotating cross-unit scheduling system, risk-based differentiation of examination packages, and an aggregate reporting mechanism integrated into the hospital’s occupational health and safety database (K3RS). The aggregated findings indicate a predominance of metabolic disorders and cardiovascular risk factors, notably dyslipidemia, hyperuricemia, elevated fasting glucose, and hypertension. The program demonstrates how internal health services can strengthen administrative coordination and support data-informed decision-making for preventive and promotive interventions, thereby sustaining workforce capacity that underpins external public service delivery. This study contributes by explicitly mapping documentary evidence of MCU implementation to Edwards’ dimensions while linking risk-based screening to organizational health data governance, an analytical combination that remains limited in empirical studies of MCU implementation in Indonesian government hospitals.